Consumers' repurchase intention in online grocery shopping in Malaysia - Sulastri, Anis Shaira (2017)
The fast technological process and development of information and communication technology (ICT) has made our lives easier in many ways especially in online business transaction. As online business continues to grow, shopping habit among Malaysian consumer has also shifted from brick and mortar stores to brick and click including grocery shopping. The trend of having grocery delivered to the doorstep is due to its convenient and time saving. Besides that, online grocery shopping has encouraged consumers to shop online to fulfill their daily household needs because people claimed that grocery shopping activity at traditional stores is stressful. Therefore, the advancement of Internet is supposed to enhance consumer loyalty and encourage them to continuously using online grocery shopping in Malaysia. Unfortunately, previous studies have shown that online groceries are not consistently purchased by Malaysian consumers due to some reasons such as inconsistent quality, high delivery charges and lack of sensory characteristics. Despite the problems faced by consumers, there are still number of them that have continuously performed online grocery shopping and the demand in the industry is still growing. Thus, this research is focused on experienced online grocery shoppers with the aim to investigate Malaysian consumers’ repurchase intention in online grocery shopping.